2022
DOI: 10.4102/jamba.v14i1.1206
|View full text |Cite
|
Sign up to set email alerts
|

Promoting sustainable development goals: Role of higher education institutions in climate and disaster management in Zimbabwe

Abstract: This article seeks to explore the role of higher education institutions (HEIs) in climate change adaptation and disaster risk management (DRM). The study is based on the qualitative desk review, thematic and document analysis and uses the theory of change to facilitate a road map for HEIs in strengthening professional human development, policy consistency in dealing with climate-induced natural disasters (CINDs) research and policies. Academic journals covering the role of HEIs in climate and disaster manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Scholars have predominantly focused on the traditional roles of HEIs, including knowledge creation and production, promotion of ideas, curricular designs related to environmental issues, collaborative efforts with NGOs, climate education and research. However, although Dzvimbo et al (2022)…”
Section: Research Gaps Identified and Research Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have predominantly focused on the traditional roles of HEIs, including knowledge creation and production, promotion of ideas, curricular designs related to environmental issues, collaborative efforts with NGOs, climate education and research. However, although Dzvimbo et al (2022)…”
Section: Research Gaps Identified and Research Problemmentioning
confidence: 99%
“…Similarly, another study examined the role of HEIs in climate change adaptation and DRM in Zimbabwe, focusing on Bindura University of Science Education and the National University of Science and Technology (NUST). The findings indicated that HEIs in Zimbabwe are involved in climate change education and DRM due to the country's susceptibility to threats posed by extreme weather events such as tropical cyclones and severe droughts (Dzvimbo et al., 2022).…”
Section: Contextual Reviewmentioning
confidence: 99%
“…Exploring the role of higher education institutions in disaster risk management and climate change adaptation [7].…”
Section: Disaster Educationmentioning
confidence: 99%
“…Increased forest fires resulting from human activities contribute to climate change (Abatzoglou & Williams 2016;Aponte, De Groot & Wotton 2016;Carnicer et al 2022;Kihila 2017), which can be disastrous if not handled properly. Natural disasters and climate change are entering a severe stage to anticipation through education which is a priority in the Sustainable Development Goals (SDGs) (Dzvimbo et al 2022;King 2011;Kupika, Mbereko & Chinokwetu 2020;Leal Filho et al 2018;Mawonde & Togo 2019). Various efforts have been made by the government so that land-clearing activities using the traditional slash-and-burn method can be avoided (Solekhan, Kunarto & Febriharini 2019).…”
Section: Introductionmentioning
confidence: 99%